Evaluation of technical quality and periapical health of root-filled teeth by using cone-beam CT - NUR, Bilge Gülsüm; OK, Evren; ALTUNSOY, Mustafa; AĞLARCI, Osman Sami; ÇOLAK, Mehmet; GÜNGÖR, Enes (Journal of Applied Oral Science, 2014)
Objective This study aimed to assess the quality of root fillings, coronal restorations, complications of all root-filled teeth and their association with apical periodontitis (AP) detected by cone-beam computed tomography (CBCT) images from an adult Turkish subpopulation. Material and Methods The sample for this study consisted of 242 patients (aging from 15 to 72 years) with 522 endodontically treated teeth that were assessed for technical quality of the root canal filling and periapical status of the teeth. Additionally, the apical status of each root-filled tooth was assessed according to the gender, dental arch, tooth type and age classification, undetected canals, instrument fracture, root fracture, apical resorption, apical lesion, furcation lesion and type and quality of the coronal structure. Statistical analysis was performed using percentages and chi-square test. Results The success rate of the root canal treatment was of 54.4%. The success rates of adequate and inadequate root canal treatment were not significantly different (p>;0.05). Apical periodontitis was found in 228 (45.6%) teeth treated for root canals. Higher prevalence of AP was found in patients aging from 20 to 29 years [64 (27%) teeth] and in anterior (canines and incisors) teeth [97 (41%) teeth]. Conclusions The technical quality of root canal filling performed by dental practitioners in a Turkish subpopulation was consistent with a high prevalence of AP. The probable reasons for this failure are multifactorial, and there may be a need for improved undergraduate education and postgraduate courses to improve the clinical skills of dental practitioners in endodontics.